Challenges and Difficulties About College Counseling in China: Response to Portnoy (2013). Issue 1 (2nd January 2016) - Zhang, Ya; Yang, Wensheng; Liu, Mingbo; Wu, Mengyang
ABSTRACT: Portnoy (2013) shared a series of personal observations about central issues in Chinese college mental health based on his Fulbright year in China. While we really appreciated his personal observations and his discussion, which shed light on cultural differences and structural forces in China, we present here a different perspective on his observations. To summarize, we describe the current situation regarding training, supervision development, and some deficiencies in Chinese college counseling, illustrate the operations of Chinese college counseling centers, and identify challenges of applying Western theory to the Eastern mental health care environment.